(Re)framing sustainable development: an ecological posture and Praxis. Issue 1 (1st January 2016) - Peterson, C. Bjørn; Knopf, Richard C.
Abstract: Sustainable development (SD) has become a catchall phrase for addressing gross economic inequality, environmental degradation, and systemic marginalization and oppression. Like all concepts, we understand the meaning and act according to the conceptual metaphors that illuminate and articulate the term SD. The attention given to the technical aspects of SD far outweighs the attention given to the way the concept has been constructed and organized as theory and practice are built. In this article, we examine the conceptual metaphors that form the foundation for SD theory and practice. We suggest that these conceptual metaphors reveal problematic understandings and assumptions. Through a conceptualization of paradigm, we describe the constituent elements as frame, worldview, and posture. We further suggest that the normative ethics found in the ecological paradigm provide a comparably superior foundation for the theory and practice of SD.